2002
DOI: 10.1002/jsfa.1182
|View full text |Cite
|
Sign up to set email alerts
|

1,3‐Dimethoxybenzene, a newly identified component of port wine

Abstract: 1,3-Dimethoxybenzene was identified by GC-O, GC-MS and Kovats indices (polar Supelcowax, 1709; non-polar Rtx-5MS, 1158) as a new volatile component of port wine. Sensory evaluation described this compound as having a sweet medicinal odour with hazelnut, resinous and woody notes. Respective threshold limits in model wine and port wine were 21 and 47 mg l À1 . Quantitative analysis by GC-MS, using a selected characteristic ion (m/z 138), indicated that young port wines from the 1998 vintage contained up to 3 mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…The structures of the compounds isolated from Aframomum arundinaceum were established using spectroscopic analysis, especially, NMR spectra in conjunction with 2D experiments, COSY, HMQC, HMBC, and direct comparison with published information and with authentic specimens obtained in our research group for some cases. The compounds isolated from the fruits of A. arundinaceum (Figure 1 ) were identified as Aframodial C 20 H 30 O 3 ( 1 ; m/z 318.2) [ 27 ], 8(17),12-labdadien-15,16-dial C 20 H 30 O 2 ( 2 ; m/z 302.2) [ 17 ], galanolactone C 20 H 30 O 3 ( 3 ; m/z 318.2) [ 27 ], galanal A C 20 H 30 O 3 ( 4 ; 15 mg, m/z 318.2) [ 28 ], and galanal B C 20 H 30 O 3 ( 5 ; m/z 318.2) [ 29 ], 1- p -menthene-3,6-diol C 10 H 18 O 2 ( 6 ; m/z 170.1; m.p:165-167°C) [ 30 ], 1,4-dihydroxybenzene C 6 H 6 O 2 ( 7 ; m/z 110.0) [ 31 ], naringenin C 15 H 12 O 5 ( 8 ; m/z 272.0; 245-248°C) [ 32 ] and kaempferol-3,7,4’-trimethylether C 18 H 16 O 6 ( 9 ; m/z 328.0; 157-158°C) [ 33 ]. The cytotoxicity of compounds 1-9 as well as the crude extracts was determined towards drug sensitive and resistant cancer cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…The structures of the compounds isolated from Aframomum arundinaceum were established using spectroscopic analysis, especially, NMR spectra in conjunction with 2D experiments, COSY, HMQC, HMBC, and direct comparison with published information and with authentic specimens obtained in our research group for some cases. The compounds isolated from the fruits of A. arundinaceum (Figure 1 ) were identified as Aframodial C 20 H 30 O 3 ( 1 ; m/z 318.2) [ 27 ], 8(17),12-labdadien-15,16-dial C 20 H 30 O 2 ( 2 ; m/z 302.2) [ 17 ], galanolactone C 20 H 30 O 3 ( 3 ; m/z 318.2) [ 27 ], galanal A C 20 H 30 O 3 ( 4 ; 15 mg, m/z 318.2) [ 28 ], and galanal B C 20 H 30 O 3 ( 5 ; m/z 318.2) [ 29 ], 1- p -menthene-3,6-diol C 10 H 18 O 2 ( 6 ; m/z 170.1; m.p:165-167°C) [ 30 ], 1,4-dihydroxybenzene C 6 H 6 O 2 ( 7 ; m/z 110.0) [ 31 ], naringenin C 15 H 12 O 5 ( 8 ; m/z 272.0; 245-248°C) [ 32 ] and kaempferol-3,7,4’-trimethylether C 18 H 16 O 6 ( 9 ; m/z 328.0; 157-158°C) [ 33 ]. The cytotoxicity of compounds 1-9 as well as the crude extracts was determined towards drug sensitive and resistant cancer cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…In a one year aged Port wine produced from Touriga Franca and Touriga Nacional grape varieties the norisoprenoid, 2,6,6-trimethylcyclohex-2-ene-1,4-dione, described as having sweet honey aroma, was identified by Rogerson et al [102]. In a young Port wine produced from Tinto Cão and Tinta Barroca grape varieties, Rogerson et al [103] identified the 1,3-dimethoxybenzene and 2-ene-1,4-dione. characterised a one year aged Touriga Nacional monovarietal Port wine as having 'plum brandy' , 'mulberry' , 'cherry' , 'wild fruits' and 'dry raisin' aromas and Guedes de Pinho et al [105] identified linalool and linalyl acetate as being the responsible for the bergamot descriptor.…”
Section: Aroma Composition and Sensory Developmentmentioning
confidence: 99%
“…It was reported to exist in the volatiles of port wine and Roquefort cheese. 23 G3 was oen used in the Suzuki coupling reaction for the preparation of metacyclophanes; however, it was a halogenated aromatic compound that belonged to the benzene-type pollutants. 24 Soaping the CMOF in the neat G1 resulted in a host-guest complex CMOFIG1.…”
Section: Structure Determination Of Liquid Moleculesmentioning
confidence: 99%